Development of clinical forensic service quality questionnaire based on SERVQUAL - Dedi Afandi; Merita Arini; Nur Hidayah; Tika Mutia; Mohammad Tegar Indrayana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Measuring service quality is an effort to assess and evaluate service performance. Currently, the measurement of clinical forensic service quality has never been done. There is no instrument for measuring service quality for clinical forensic patients. Objectives: This study aims to collect valid evidence of a modified questionnaire to measure clinical forensic service quality. Methods: This study protocol followed three phases from the World Health Organization guidelines on translating and adapting instruments for substance abuse. The study was conducted at Bhayangkara Hospital Pekanbaru, with ten respondents in phase pretesting and thirty in phase evaluation of the internal structure. The questionnaire developed was from the original version of SERVQUAL, consisting of 5 dimensions (reliability, responsiveness, assurance, empathy, and tangible) and 22 items with a five Likert scale. Content validity, response process, and internal structure are applied to collect valid evidence.Results: A modified SERVQUAL questionnaire was obtained for clinical forensic patients with 22 items through an expert panel and respondent interview. The majority had high validity (item to total correlation coefficient r > 0.6). This final version showed excellent internal consistency (Cronbach alpha 0.956). Conclusion: The final version of the modified SERVQUAL for clinical forensic service quality questionnaire has sufficient validity evidence for its content, response process, and some part of its internal structure, namely item to total correlation and reliability.